(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The publication of Hijos de los 70: historias de la generación que heredó la tragedia, by journalists Carolina Arenes and Astrid Pikielny, published in 2016 by Sudamericana, was a hinge in the visibilization of “missing voices” in the debate on the recent past in Argentina. In the search to reinstate the polyphonic character inherent to the figure of “children”, the authors proposed a textual “dialogue” between children of the disappeared and former militants, children of people murdered by armed organizations and children of people convicted of crimes against humanity. This article aims at restoring the editorial and political plot of the book, paying attention to the motivations, references and readers expected by the authors, the editorial criteria referred to the production, as well as the forms of reception and circulation that the book had among the public and among the protagonists.